Políticas de habitabilidad en calle en Bogotá, Colombia ¿hacia el desarrollo humano integral? (2018)
Homelessness in Bogotá (Colombia) is a historical social phenomenon. To address this issue, policies has been formulated based on the acknowledgement of street inhabitants as legal subjects. However, despite this policy development, this population group has suffered violence perpetrated by both civil society and the State. The purpose of this research is to analyze the way in which policies for homelessness either contribute to their integral human development or transgress their life. The theoretical bases for analysis are the theory of human integral development, through a qualitative methodological approach. The results concludedthat policy has contributed to integral human development only for homeless population that are already under the protection of an Attention Center, while simultaneously perpetrating violence against people who have chosen the streets as their life project